2019
DOI: 10.1021/acs.jpcc.9b08892
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Excitons and Polarization of Dielectric Nanoparticles

Abstract: Indirect excitons (IX) are widely studied for the purpose of fundamental physics such as Bose−Einstein condensate formation and to develop new devices for photovoltaics, conversion, accumulation, and transport of energy and the creation of quantum-optical and exciton devices. The excitons in dielectric nanoparticles (NPs) determine the nanosystem physical properties, which strongly depend on NP polarizability. It can take the high values even when interacting with low-intensity radiation. In article, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They are bounded from above by the boundary of the spectrum max 1, () l Ea Mechanisms underlying the formation of the interband and intraband absorption (emission) spectra in a nanosystem are proposed. It is shown that spectra of interband absorption (emission) consist of energy bands that are formed by electron transitions between quasi-stationary and stationary states, and intraband absorption spectra consist of zones that appear due to electron transitions between stationary states [5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…They are bounded from above by the boundary of the spectrum max 1, () l Ea Mechanisms underlying the formation of the interband and intraband absorption (emission) spectra in a nanosystem are proposed. It is shown that spectra of interband absorption (emission) consist of energy bands that are formed by electron transitions between quasi-stationary and stationary states, and intraband absorption spectra consist of zones that appear due to electron transitions between stationary states [5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the fact that the class of 2D materials presents some distinctive features, which are highly dissimilar in comparison with those of their threedimensional (3D) correspondents, it is used for the next-generation ultra-thin electronics [88]. In this context some researchers explained the role of the expansion of indirect excitons (an indirect exciton-IX-is a bound pair of an electron and hole in separated QW layers [89]), which is observed in vdW transition metal dichalcogenide (TMD) heterostructures at room temperature, this study helping for the progress of excitonic devices with energy-productive computation and ideal connection quality for optical communication cases [90,91]. Various theoretical and experimental analyses have been developed for the improvement of the excitonic devices that use IXs propagation in different types of single QWs and coupled QWs [92,93].…”
Section: Excitons and Biexcitons In Two-dimensional Semiconductor Strmentioning
confidence: 99%